2020
DOI: 10.3828/msmi.2020.4
|View full text |Cite
|
Sign up to set email alerts
|

Sound in Horror Film Trailers

Abstract: In this paper I analyse the soundtracks of fifty horror film trailers, combining formal analysis of the soundtracks with quantitative methods to describe and analyse how sound creates a dominant emotional tone for audiences through the use of different types of sounds (dialogue, music, and sound effects) and the different sound envelopes of affective events. The results show that horror trailers have a three-part structure that involves establishing the narrative, emotionally engaging the audience, and communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Brotto (2013, 155) observed that computational methods for exploring film style lacked a method for analyzing sound. Despite an abundance of freely available audio analysis tools developed in the fields of bioacoustics, soundscape ecology, and computational music analysis, few (Ma et al 2021;Moncrieff, Dorai, and Venkatesh 2002;Pfeiffer and Srinivasan 2002;Redfern 2020aRedfern , 2020bRedfern , 2021 have attempted to apply these technologies to the analysis of motion picture soundtracks.…”
mentioning
confidence: 99%
“…Brotto (2013, 155) observed that computational methods for exploring film style lacked a method for analyzing sound. Despite an abundance of freely available audio analysis tools developed in the fields of bioacoustics, soundscape ecology, and computational music analysis, few (Ma et al 2021;Moncrieff, Dorai, and Venkatesh 2002;Pfeiffer and Srinivasan 2002;Redfern 2020aRedfern , 2020bRedfern , 2021 have attempted to apply these technologies to the analysis of motion picture soundtracks.…”
mentioning
confidence: 99%
“…The similarities in the audio-visual part of the Indonesian horror movie trailers, at least from the ten movies whose trailers we are about to discuss here, lie in them employing a rather dark tone colour to present the visuals, as is common within the genre both in Indonesian and international horror movies and trailers. Meanwhile, the background music and sound are slowly intensifying from the introduction up to the third part of the trailers, which are also common within the genre (Redfern, 2020). Redfern (2020) pointed out that these movie producers may also go out of their way to mash-up sounds and music so that their movies can have a set of sound effects and music specially tailored to the movies themselves.…”
mentioning
confidence: 99%
“…Meanwhile, the background music and sound are slowly intensifying from the introduction up to the third part of the trailers, which are also common within the genre (Redfern, 2020). Redfern (2020) pointed out that these movie producers may also go out of their way to mash-up sounds and music so that their movies can have a set of sound effects and music specially tailored to the movies themselves.…”
mentioning
confidence: 99%